PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KEADILAN DISTRIBUTIF ANGGARAN SEBAGAI VARIABEL INTERVENING (STUDI PADA RUMAT SAKIT ESTOMIHI MEDAN) - Hendrik E. S. Samosir (JURNAL ILMIAH MAKSITEK, 2018)
This research is a field research conducted at Estomihi Hospital. This study takes the title: "The Influence of Budgeting Participation on Managerial Performance with Distributive Budget Justice as an Intervening Variable (Study at Medan Estomihi Hospital)". The population in this study were all employees who contributed to the budget preparation process in 2018 in each section with a total of 40 employees. The purpose of this research is to find out how the influence of budget participation has an impact on managerial performance directly or through budget distributive justice. Based on the results of research and data analysis, the conclusions are: budget participation has a positive and significant influence on distributive justice and managerial performance while distributive justice does not have a significant impact on changes in managerial performance